The human Aurora kinase inhibitor danusertib is a lead compound for anti-trypanosomal drug discovery via target repurposing - Ochiana, Stefan O. (2012)
New drugs for neglected tropical diseases such as human African trypanosomiasis (HAT) are needed, yet drug discovery efforts are not often focused on this area due to cost. Target repurposing, achieved by the matching of essential parasite enzymes to those human enzymes that have been successfully inhibited by small molecule drugs, provides an attractive means by which new drug optimization programs can be pragmatically initiated. In this report we describe our results in repurposing an established class of human Aurora kinase inhibitors, typified by danusertib (1), which we have observed to be an inhibitor of trypanosomal Aurora kinase 1 (TbAUK1) and effective in parasite killing in vitro. Informed by homology modeling and docking, a series of analogs of 1 were prepared that explored the scope of the chemotype and provided a nearly 25-fold improvement in cellular selectivity for parasite cells over human cells.